(untitled) (Swiss Medical Weekly, 2012)
QUESTION UNDER STUDY: To investigate pregnancy related changes of rheumatoid factor (RF) isotypes and anti-citrullinated protein antibodies (ACPA) and their association with disease activity and therapy in patients with rheumatoid arthritis. METHODS: In 22 rheumatoid arthritis patients disease activity (DAS28-CRP), therapy as well as the levels of rheumatoid factor isotypes (IgG, IgA, IgM) and ACPA were analysed longitudinally within 4 months before conception, once at each trimester and at 6,12 and 24 weeks postpartum. In addition, immunoglobulin isotypes (IgG, IgA, IgM) were measured in the pregnant rheumatoid arthritis patients as well as in 29 healthy pregnant women at the time points mentioned above. RESULTS: Our results showed that pregnancy significantly reduced systemic levels of the immunoglobulin isotypes IgG and IgA, but did not change the levels of IgG-RF, IgA-RF nor those of IgG-ACPA using assays with different antigen preparations. However, patients with active disease before and during pregnancy showed significantly higher levels of ACPA as compared to patients with low disease activity during pregnancy. Significantly more patients with low disease activity during pregnancy received pregnancy compatible disease modifying antirheumatic drugs or TNF-inhibitor therapy within four months before conception (P = 0.025). CONCLUSIONS: Our results suggest that treatment should be adjusted to pregnancy compatible drugs preconceptionally and continued until conception and beyond to allow for stable inactive disease during gestation and control the levels of autoantibodies.